Population balance modeling of growth and agglomeration of crystals in racemic mixtures - Loppinet, Elise Marie Nicolette (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Ανάλυσης, Σχεδιασμού και Ανάπτυξης Διεργασιών και Συστημάτων (ΙΙ), 2018)
Crystallization is a separation technique present in multiple applications ranging from industrial applications in the food, petroleum and pharmaceutical industries. It is used both in the production of pharmaceutical molecules and the purification, stabilization and definition of the desired properties of the final product. When the compounds are enantiomeric where the presence of one enantiomer may affect the properties of the other, it is important to have processes capable of separating the enantiomers, or ideally, only producing one enantiomer. During crystallization, four sub-mechanisms usually take place i.e. nucleation, growth-dissolution, breakage and agglomeration. While the first three of these mechanisms have been modelled extensively, agglomeration has often posed difficulties in solving and therefore despite its important effect on particle size it is often considered negligible. In most processes however, far from being negligible, agglomeration is of utmost importance. For example, it is of particular importance in Viedma ripening, a process during which a racemic mixture, i.e. a solution containing both enantiomers of a compound, attains enantiopurity through grinding of the crystals. The aim of this thesis was to create a mathematical model capable of describing a system in which agglomeration is an active mechanism alongside growth and breakage, using population balances. The model was built and solved using the Comsol Multiphysics software package. Using this model the effect of agglomeration during crystallization was elucidated, while its interplay with growth and breakage where also studied. When growth and agglomeration are included in the model, the number of particles present in the solution decreases over time while the average particle size increases. Additionally the total crystal mass in the solution increases over time. While both growth and agglomeration lead to larger particles, growth alone cause the increase in crystal mass, while agglomeration is the cause of the change in crystal number. After an analysis of the growth rate and agglomeration parameters, a breakage rate was added to the model. The larger the breakage rate the higher 5 the number of particles in the solution at the end of the simulation. The average particle size decreased with the presence of the breakage sub-mechanism.